Preparation method of red blood cell membrane modified tungsten disulfide quantum dot composite material and application thereof
Patent Information
- Application Number
- CN202310698583.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2023-06-13
- Publication Date
- 2026-11-03
- Estimated Expiration
- 2043-06-13
AI Technical Summary
Existing nanomedicines tend to accumulate in the body, making it difficult to cross biological barriers and activate the immune recognition system. This leads to accelerated immune clearance upon repeated administration, limiting their clinical application.
Tungsten disulfide quantum dots (WS2 QDs/RBC nanocomposite material) modified with red blood cell membranes were prepared by electrostatic adsorption, which improved biocompatibility, enhanced immune escape ability, and reduced aggregation.
It effectively penetrates the blood-brain barrier, reduces abnormal Aβ deposition, alleviates Alzheimer's symptoms, reduces immunogenicity, improves stability and targeted delivery capabilities, enhances photothermal conversion capabilities, and reduces Aβ fibrillary concentration.
Smart Images

Figure CN116688150B_ABST
Abstract
Description
Technical Field
[0001] This invention belongs to the fields of materials synthesis and biomedicine, specifically relating to a method for preparing WS2 QDs / RBC nanocomposite materials and their applications. Background Technology
[0002] Alzheimer's disease has been recognized by the World Health Organization as a major global public health issue. Synthetic nanoparticles have become a research hotspot due to their high drug loading capacity, controllable particle size, sustained drug release, and unique properties. Some nanoparticles, with their superior physicochemical properties, can be applied to the treatment of Alzheimer's disease. Compared to traditional Alzheimer's drugs, nanoparticle drugs can better penetrate the blood-brain barrier, reach the brain, and exert their effects. Furthermore, due to their excellent photothermal conversion capabilities, they can also depolymerize Aβ fibrils in the brain, leading to better treatment of Alzheimer's disease. Moreover, these nanoparticles also exhibit high biocompatibility and low toxicity.
[0003] Tungsten disulfide quantum dots are a type of nanomaterial with excellent properties, characterized by small particle size, large specific surface area, strong photothermal conversion performance, and resistance to ROS and the ability to inhibit Aβ monomer aggregation. This is the main approach of tungsten disulfide quantum dots in treating Alzheimer's disease. They can effectively eliminate oxidizing substances such as hydroxyl radicals, superoxide radicals, and hydrogen peroxide in the body, reduce oxidative stress, and, more importantly, reduce abnormal Aβ deposition, thereby alleviating the symptoms of Alzheimer's disease.
[0004] However, nanomedicines still have some unresolved drawbacks. Scientists have discovered that these nanomedicines tend to aggregate easily in the body and still cannot cross some biological barriers, which greatly limits their clinical application. Furthermore, exogenous nanoparticles can activate the body's immune recognition system, leading to accelerated immune clearance upon repeated administration. Therefore, improving the biocompatibility and targeted delivery capabilities of nanoparticles, while reducing their immunogenicity, has become a key step in solving this problem. Summary of the Invention
[0005] To address the shortcomings of existing technologies, this invention provides a method for preparing WS2 QDs / RBC nanocomposite materials. The composite material uses nano-sized tungsten disulfide quantum dots (WS2 QDs) as a matrix. Red blood cell membranes are broken down and centrifuged using differential centrifugation to obtain red blood cell membrane vesicles, which are then prepared via electrostatic adsorption to obtain the WS2 QDs / RBC nanocomposite material. This material exhibits ROS resistance and Cu chelation properties. 2+This material possesses the ability to inhibit Aβ monomer aggregation and photothermally depolymerize Aβ fibrils, thereby treating Alzheimer's disease. Modifying this material with erythrocyte membranes can effectively evade the body's immunogenicity recognition, effectively improve the aggregation of WS2 QDs under physiological conditions, reduce plasma protein adsorption, and enhance immune escape.
[0006] The preparation method of the WS2 QDs / RBC nanocomposite material provided by the present invention is carried out according to the following steps:
[0007] (1) Dissolve commercially available nano-sized WS2 QDs powder in pure water and disperse it evenly by ultrasonication to obtain WS2 QDs dispersion;
[0008] Preferably, the ultrasound in step (1) is performed using an ultrasonic cell disruptor in an ice-water bath, with an ultrasonic power of 150W-300W and an ultrasound time of 0.1h-1.0h.
[0009] Preferably, the WS2 QDs particle size in the WS2 QDs dispersion in step (1) is less than 60 nm; the concentration of the WS2 QDs dispersion is 0.1-2 mg / ml.
[0010] (2) Animal blood was extracted as a raw material for preparing red blood cell membranes; then the blood was mixed with heparin sodium solution to obtain a mixture;
[0011] Preferably, the animal blood in step (2) is from mice, and the mouse species is any one of female BALB / c, female ICR, female C3H, and female RF; the volume ratio of the blood to the heparin sodium solution is 15-80:1; and the mass concentration of the heparin sodium solution is 10 mg / ml.
[0012] (3) Centrifuge the mixture obtained in step (2), collect the precipitate, add PBS and centrifuge and wash several times. The precipitate is the pure red blood cells. Then add low concentration PBS again to break the red blood cells. After standing, the red blood cell membrane rupture solution is obtained.
[0013] Preferably, the centrifugation speed in step (3) is 2000 rpm / min-5000 rpm / min, and the centrifugation time is 5 min-20 min; the settling temperature is 0-4℃, and the settling time is 0.5 h-2 h.
[0014] Preferably, in step (3), the concentration of PBS used during centrifugation and washing is 0.01M, and the number of washing cycles is 3-5; when adding PBS to break down red blood cells, the concentration of low-concentration PBS used is 0.0025M.
[0015] (4) Centrifuge the cell membrane disruption solution obtained in step (3), then collect the precipitate, add PBS to wash several times, then wash with pure water, collect the precipitate, add PBS again to dissolve, and sonicate to disperse evenly to obtain red blood cell membrane dispersion.
[0016] Preferably, in step (4), the centrifugation speed is 5000 rpm / min-14000 rpm / min and the centrifugation time is 10 min-30 min; the ultrasound is performed under ice-water bath conditions, the ultrasound power is 100W-300W and the ultrasound time is 0.1h-1.0h.
[0017] The concentration of the PBS is 0.01M; the concentration of the red blood cell membrane dispersion is 100mg / ml.
[0018] (5) Mix the WS2 QDs dispersion obtained in step (1) and the red blood cell membrane dispersion in step (4) in a certain proportion, stir overnight under constant temperature, then centrifuge to discard the supernatant, collect the precipitate and add PBS solution, and sonicate to disperse evenly to obtain WS2 QDs / RBC dispersion, which is WS2 QDs / RBC nanocomposite material (red blood cell membrane modified tungsten disulfide quantum dot composite material).
[0019] Preferably, the mass ratio of the erythrocyte membrane in the erythrocyte membrane dispersion and the tungsten disulfide quantum dots in the WS2 QDs dispersion in step (5) is 10:1-100:1.
[0020] Preferably, the temperature for overnight constant temperature stirring in step (5) is 37°C, and the stirring rate is 50-200 rpm; the ultrasonic power for ultrasonic dispersion is 100W-300W, the ultrasonic time is 0.1h-1.0h, and the conditions are ice-water bath; the concentration of the WS2QDs / RBC dispersion is 0.1-2mg / ml (calculated based on the mass of WS2 QDs).
[0021] The WS2 QDs / RBC nanocomposite material prepared in this invention is used in the preparation of anti-Alzheimer's disease drugs.
[0022] Compared with the prior art, the beneficial effects of the present invention are mainly reflected in:
[0023] 1) Employing Cu with excellent photothermal conversion performance 2+WS2 QDs, with their chelating ability, anti-ROS properties, and ability to inhibit Aβ monomer aggregation, are used to treat Alzheimer's disease. Compared with traditional drugs, WS2 QDs / RBC nanocomposites themselves have the ability to eliminate oxides such as hydroxyl radicals, and can also adsorb copper ions to reduce Aβ toxicity. At the same time, under the irradiation of near-infrared laser, the material converts light energy into heat energy to depolymerize Aβ fibrils and reduce the concentration of Aβ fibrils in the brain. This combination is used to treat Alzheimer's disease.
[0024] 2) Red blood cells are widely distributed in various tissues and organs of the human body, with diverse sources, and the preparation of red blood cell membranes is simple. Modifying WS2 QDs with red blood cell membranes can not only improve their stability under physiological conditions, but also allow them to evade phagocytosis by their own macrophages, achieving a long circulation effect in the body. This makes the nanomedicines less prone to aggregation in the body and allows them to reach the lesion site more effectively.
[0025] 3) This invention uses a combination of 37°C shaking incubation and cell disruption sonication to prepare WS2 QDs / RBC dispersion. Shaking incubation facilitates the adsorption of cell membranes on the surface of WS2 QDs, while cell disruption sonication helps control the cell membrane and the particle size of WS2 QDs / RBCs. Compared with the conventional extrusion method, this method is simple to operate and has good reproducibility. Attached Figure Description
[0026] Figure 1 These are TEM images of WS2 QDs(a) and WS2 QDs / RBC(b) in Example 1;
[0027] Figure 2 This is a Zata potential diagram of WS2 QDs, RBC, and WS2 QDs / RBC;
[0028] Figure 3 The first row shows the stability images of WS2 QDs in Example 1 after 24h (a) and 48h (b) in pure water (left), PBS buffer at pH 7.4 (middle), and RPMI-1640 medium containing 10% fetal bovine serum (right).
[0029] The second row shows the stability images of WS2 QDs / RBC in Example 1 after 24 h (c) and 48 h (d) in pure water (left), PBS buffer at pH 7.4 (middle), and RPMI-1640 medium containing 10% fetal bovine serum (right).
[0030] Figure 4 The graphs show the photothermal temperature rise curves of WS2 QDs (a) and WS2 QDs / RBC (b) under different concentration conditions (0.2 mg / ml, 0.1 mg / ml, 0.05 mg / ml) in Example 1.
[0031] Figure 5 Figure a shows the UV absorption curves of hydroxyl elimination performance, where curve A is the UV absorption curve of the control group, curve B is the UV absorption curve of the hydroxyl elimination performance of WS2 QDs, and curve C is the UV absorption curve of the hydroxyl elimination performance of WS2 QDs / RBC; Figure b shows the UV absorption peaks corresponding to the three curves in figure a.
[0032] Figure 6 Figure a shows the SOD enzyme-like activity fluorescence curves, where curve A is the SOD enzyme-like activity fluorescence curve of the control group, curve B is the SOD enzyme-like activity fluorescence curve of WS2 QDs, and curve C is the SOD enzyme-like activity fluorescence curve of WS2 QDs / RBC; Figure b shows the fluorescence peaks corresponding to the three curves in figure a.
[0033] Figure 7 Figure a shows the UV absorption curves of CAT enzyme-like activity; curve A is the UV absorption curve of CAT enzyme-like activity in the control group, curve B is the UV absorption curve of CAT enzyme-like activity in WS2 QDs, and curve C is the UV absorption curve of CAT enzyme-like activity in WS2 QDs / RBC; Figure b shows the UV absorption peaks corresponding to the three curves in figure a.
[0034] Figure 8 Cu of WS2 QDs and WS2 QDs / RBC 2+ Chelation performance graph; where graph a shows the determination of Cu chelation performance of WS2 QDs. 2+ Cu 2+ The standard curve; Figure c shows the determination of WS2 QDs / RBC chelated Cu. 2+ Cu 2+ The standard curve; Figure b shows the Cu content when determining WS2 QDs and WS2 QDs / RBC. 2+ The remaining Cu in the chelation solution 2+ Concentration; d plot shows Cu in WS2 QDs and WS2QDs / RBC 2+ Chelation percentage;
[0035] Figure 9 Figure a shows the ThT fluorescence curves for inhibiting Aβ monomer aggregation; curve A is the ThT fluorescence curve for the control group inhibiting Aβ monomer aggregation, curve B is the ThT fluorescence curve for WS2 QDs inhibiting Aβ monomer aggregation, and curve C is the ThT fluorescence curve for WS2 QDs / RBC inhibiting Aβ monomer aggregation; Figure b shows the fluorescence peaks corresponding to the three curves in figure a.
[0036] Figure 10Figure a shows the ThT fluorescence curves of Aβ fibrils (A), Aβ fibrils + NIR (B), Aβ fibrils + WS2 QDs (C), and Aβ fibrils + WS2 QDs + NIR (D); Figure b shows the fluorescence peaks corresponding to the four curves in Figure a; Figure c shows the ThT fluorescence curves of Aβ fibrils (A), Aβ fibrils + NIR (B), Aβ fibrils + WS2 QDs / RBC (C), and Aβ fibrils + WS2 QDs / RBC + NIR (D); Figure d shows the fluorescence peaks corresponding to the four curves in Figure c.
[0037] Figure 11 These are laser confocal fluorescence images of WS2 QDs / RBC nanocomposites taken up by cells; in image a, WS2 QDs / RBCs stained with PE-FITC appear green; in image b, SY5Y cell nuclei stained with DAPI appear blue; and in image c, fluorescence images of WS2 QDs / RBCs after being taken up by cells.
[0038] Figure 12 The survival rate of cells after incubation with different concentrations (3.125 μg / ml, 6.25 μg / ml, 12.5 μg / ml, 25 μg / ml, 50 μg / ml) of WS2QDs and WS2 QDs / RBCs for 24 h is shown. Detailed Implementation
[0039] Various exemplary embodiments of the present invention will now be described in detail. This detailed description should not be considered as a limitation of the present invention, but rather as a more detailed description of certain aspects, features, and embodiments of the present invention.
[0040] It should be understood that the terminology used herein is merely for describing particular embodiments and is not intended to limit the invention. Unless otherwise stated, all technical and scientific terms used herein have the same meaning as commonly understood by one of ordinary skill in the art. While only preferred methods and materials have been described herein, any methods and materials similar or equivalent to those described herein may be used in the implementation or testing of this invention. All references to this specification are incorporated by way of citation to disclose and describe methods and / or materials associated with those references. In the event of any conflict with any incorporated reference, the content of this specification shall prevail.
[0041] Various modifications and variations can be made to the specific embodiments described in this specification without departing from the scope or spirit of the invention, as will be apparent to those skilled in the art. Other embodiments derived from this specification will also be readily apparent to those skilled in the art. This specification and embodiments are merely exemplary.
[0042] Example 1:
[0043] (1) Disperse commercially available nano-sized WS2 QDs powder in pure water, and use an ultrasonic cell disruptor to sonicate it for 0.5 h under ice-water bath conditions and ultrasonic power of 300W to make it uniformly dispersed (WS2 QDs particle size is less than 60nm) to obtain WS2QDs dispersion with a concentration of 1mg / ml.
[0044] (2) 4 ml of blood was collected from the eyeballs of female Balb / c mice, and 100 μl of heparin sodium solution was added to the centrifuge tube to obtain a mixture for later use.
[0045] (3) Centrifuge the obtained mixture (3000 r / min, 10 min), discard the supernatant, disperse the precipitate with 0.01 M PBS, repeat centrifugation and washing three times (3800 r / min, 5 min) to obtain pure red blood cells, then add 0.0025 M PBS and let stand at 4℃ for 0.5 h to break the red blood cell membrane and obtain red blood cell membrane rupture solution;
[0046] (4) Take out the erythrocyte membrane disruption solution obtained in (3) and centrifuge (14000 r / min, 30 min). Disperse the resulting precipitate with 0.01 M PBS, centrifuge and wash twice, then wash once with pure water (14000 r / min, 10 min). Collect the precipitate, weigh it accurately, add 0.01 M PBS (pH = 7.4) to dissolve it, and use an ultrasonic disruptor to disperse it evenly to obtain erythrocyte membrane dispersion (100 mg / ml).
[0047] (5) Mix 2 ml (1 mg / ml) of WS2 QDs dispersion obtained in step (1) and 1 ml (100 mg / ml) of red blood cell membrane dispersion obtained in step (4), place them in a constant temperature shaker and stir overnight (37°C) at a shaking rate of 100 rpm, then centrifuge and discard the supernatant. Disperse the precipitate with PBS solution and use cell disruption sonication to disperse it evenly. The sonication power is 250 W and the sonication time is 0.3 h. Place in an ice water bath. The resulting dispersion is the WS2 QDs / RBC nanocomposite material (0.5 mg / ml, calculated based on the mass of WS2 QDs).
[0048] Figure 1 TEM images of WS2 QDs (a) and WS2 QDs / RBCs (b) prepared in Example 1 show that the particle size of WS2 QDs is less than 60 nm and there is no obvious aggregation. The particle size of the erythrocyte membrane is 100 ± 2.3 nm. The particle size of WS2 QDs / RBCs is 150 ± 2.6 nm, indicating that the surface of WS2 QDs was successfully modified by the erythrocyte membrane.
[0049] Figure 2Potential plots of WS2 QDs, RBCs, and WS2 QDs / RBCs are shown to characterize the stability of the nanocomposite materials. The potential of WS2 QDs is -38.5 mV, that of RBC is -30.6 mV, and that of WS2 QDs / RBC is -30.4 mV. The surface potentials of RBCs and WS2 QDs / RBCs are very close, indicating that WS2 QDs are uniformly modified by the erythrocyte membrane, i.e., coated on the outer surface of WS2 QDs. Meanwhile... Figure 1 In (b), it can also be clearly seen that the erythrocyte membrane was successfully modified on the surface of WS2 QDs and was uniformly covered.
[0050] like Figure 3 As shown in the figure, the stability test results show that after 24h and 48h, WS2 QDs showed obvious precipitation in the three media, while the WS2 QDs / RBC dispersion was clear and free of precipitation. Therefore, it is indicated that the modified nanocomposite material has increased dispersibility and stability under physiological conditions.
[0051] Example 2:
[0052] (1) The commercially available nano-sized WS2 QDs powder was dispersed in pure water and ultrasonically dispersed for 0.7 h in an ice-water bath at an ultrasonic power of 200W to make it uniform (WS2 QDs particle size is less than 60nm); the concentration of the WS2QDs dispersion was 0.5mg / ml.
[0053] (2) 4 ml of blood was collected from the eyeballs of female ICR mice, and 150 μl of heparin sodium was added to the centrifuge tube to obtain a mixture for later use.
[0054] (3) Centrifuge the obtained mixture (2000 r / min, 20 min), discard the supernatant, disperse the precipitate with 0.01 M PBS, repeat centrifugation and washing three times (3000 r / min, 15 min) to obtain pure red blood cells, add 0.0025 M PBS to the red blood cell precipitate and place it in a 0℃ refrigerator for 2 h to break the red blood cells and obtain red blood cell membrane rupture solution;
[0055] (4) Take out the erythrocyte membrane disruption solution obtained in (3) and centrifuge (11000 r / min, 40 min). Disperse the resulting precipitate with 0.01 M PBS, centrifuge and wash twice, then wash once with pure water (11000 r / min, 15 min). Collect the precipitate, weigh it accurately, add 0.01 M PBS (pH = 7.4) to dissolve it, and use an ultrasonic disruptor to disperse it evenly to obtain erythrocyte membrane dispersion (100 mg / ml).
[0056] (5) Mix 2 ml (0.5 mg / ml) of WS2 QDs dispersion obtained in step (1) and 1 ml (100 mg / ml) of red blood cell membrane dispersion obtained in step (4), place in a constant temperature shaker and stir overnight (37°C) at a shaking rate of 200 rpm, then centrifuge and discard the supernatant. Disperse the precipitate with PBS solution and use cell disruption sonication to disperse it evenly. The sonication power is 300 W and the sonication time is 0.5 h. Place in an ice water bath. The resulting dispersion is the WS2 QDs / RBC nanocomposite material (0.5 mg / ml, calculated based on the mass of WS2 QDs).
[0057] Particle size measurements showed that the particle size of WS2 QDs was 49.1 ± 2.3 nm, and the WS2 QDs / RBC particle size was 163.5 ± 2.6 nm. The potential of WS2 QDs was -43.6 mV, the cell membrane potential was -28.6 mV, and the WS2 QDs / RBC potential was -30.1 mV.
[0058] Example 3:
[0059] (1) The commercially available nano-sized WS2 QDs powder was dispersed in pure water and ultrasonically dispersed for 1 hour under ice-water bath conditions and ultrasonic power of 100W to make it uniform (WS2 QDs particle size is less than 60nm); the concentration of the WS2 QDs dispersion was 0.1mg / ml.
[0060] (2) 4 ml of blood was collected from the eyeballs of female C3H mice, and 50 μl of heparin sodium was added to the centrifuge tube to obtain a mixture for later use.
[0061] (3) Centrifuge the obtained mixture (3000 r / min, 10 min), discard the supernatant, disperse the precipitate with 0.01 M PBS, repeat centrifugation and washing three times (4500 r / min, 5 min) to obtain pure red blood cells, add 0.0025 M PBS to the red blood cell precipitate and place it in a 2℃ refrigerator for 1 h to break the red blood cells and obtain red blood cell membrane rupture solution;
[0062] (4) Centrifuge the erythrocyte membrane disruption solution obtained in (3) (8000 r / min, 50 min), disperse the resulting precipitate with 0.01 M PBS, centrifuge and wash twice, then wash once with pure water (8000 r / min, 20 min), collect the precipitate, weigh it accurately, add 0.01 M PBS (pH = 7.4) to dissolve it, and use an ultrasonic disruptor to disperse it evenly to obtain erythrocyte membrane dispersion (100 mg / ml);
[0063] (5) Mix 5 ml (0.1 mg / ml) of WS2 QDs dispersion obtained in step (1) and 0.05 ml (100 mg / ml) of red blood cell membrane dispersion obtained in step (4), place in a constant temperature shaker and stir overnight (37°C) at a shaking rate of 50 rpm, then centrifuge and discard the supernatant, disperse the precipitate with PBS solution and use cell disruption sonication to disperse it evenly, sonication power 100 W, sonication time 1 h, ice water bath, the resulting dispersion is WS2 QDs / RBC nanocomposite material (0.5 mg / ml, calculated based on the mass of WS2 QDs).
[0064] Particle size measurements showed that the particle size of WS2 QDs was 53.6 ± 1.5 nm, and the WS2 QDs / RBC particle size was 167.5 ± 2.2 nm. The potential of WS2 QDs was -41.7 mV, the cell membrane potential was -33.2 mV, and the WS2 QDs / RBC potential was -34.1 mV.
[0065] Example 4:
[0066] (1) The commercially available nano-sized WS2 QDs powder was dispersed in pure water and ultrasonically dispersed for 0.8 h under ice-water bath conditions and ultrasonic power of 150W to make it uniform (WS2 QDs particle size is less than 60nm); the concentration of the WS2QDs dispersion was 2mg / ml.
[0067] (2) 4 ml of blood was collected from the eyeballs of female RF mice, and 300 μl of heparin sodium was added to the centrifuge tube to obtain a mixture for later use;
[0068] (3) Centrifuge the obtained mixture (4000 r / min, 5 min), discard the supernatant, disperse the precipitate with 0.01 M PBS, repeat centrifugation and washing three times (5000 r / min, 5 min) to obtain pure red blood cells, add 0.0025 M PBS to the red blood cell precipitate and place it in a 3℃ refrigerator for 1.5 h to break the red blood cells and obtain red blood cell membrane lysis solution;
[0069] (4) Centrifuge the erythrocyte membrane disruption solution obtained in (3) (5000 r / min, 60 min), disperse the resulting precipitate with 0.01 M PBS, centrifuge and wash twice, then wash once with pure water (5000 r / min, 40 min), collect the precipitate, weigh it accurately, add 0.01 M PBS (pH = 7.4) to dissolve it, and use an ultrasonic disruptor to disperse it evenly to obtain erythrocyte membrane dispersion (100 mg / ml);
[0070] (5) Mix 1 ml (2 mg / ml) of WS2 QDs dispersion obtained in step (1) and 0.6 ml (100 mg / ml) of red blood cell membrane dispersion obtained in step (4), place in a constant temperature shaker and stir overnight (37°C) at a shaking rate of 150 rpm, then centrifuge and discard the supernatant, disperse the precipitate with PBS solution and use cell disruption sonication to disperse it evenly, sonication power 150 W, sonication time 0.8 h, ice water bath, the resulting dispersion is WS2 QDs / RBC nanocomposite material (0.5 mg / ml, calculated based on the mass of WS2 QDs).
[0071] Particle size measurements showed that the particle size of WS2 QDs was 51.6 ± 1.9 nm, and the WS2 QDs / RBC particle size was 154.3 ± 2.4 nm. The potential of WS2 QDs was -40.6 mV, the cell membrane potential was -31.5 mV, and the WS2 QDs / RBC potential was -32.1 mV.
[0072] Performance evaluation (taking the composite material prepared in Example 1 as an example):
[0073] (1) Irradiation heating curve of WS2 QDs / RBC nanocomposite material;
[0074] The WS2 QDs and WS2 QDs / RBC in Example 1 were diluted to different concentrations with pure water, and then analyzed using a near-infrared laser (2W / cm²). 2 Irradiated with WS2 QDs (808 nm) for 10 min, and the temperature was recorded every 30 s. The photothermal conversion capacity of WS2 QDs (a) and WS2 QDs / RBC (b) at different concentrations was investigated and plotted.
[0075] The results are as follows Figure 4 As shown, with pure water as a control, the heating rate of WS2 QDs at different concentrations is extremely fast, and the temperature is positively correlated with the concentration, reaching a maximum of 61℃. The WS2 QDs / RBC nanocomposite material can also reach a maximum of 51.4℃, which can be used as an ideal photothermal agent.
[0076] (2) ROS resistance of WS2 QDs / RBC nanocomposites;
[0077] ① Assessment of hydroxyl radical scavenging ability: Salicylic acid (SA) can react with hydroxyl radicals generated by the Fenton reaction to produce 2,3-dihydroxybenzoic acid, which exhibits strong ultraviolet absorption at 510 nm. This property was used to assess the material's ability to scavenge hydroxyl radicals. A suitable amount of 1.8 mM FeSO4 and 5 mM H2O2 were fully reacted, and then added to WS2 QDs and WS2QDs / RBC from Example 1, respectively. The mixture was placed in a 37°C constant temperature shaking incubator and reacted for 1 h. Then, a suitable amount of 1.8 mM SA was added and the mixture was reacted for 30 min. The ultraviolet absorption of 2,3-dihydroxybenzoic acid was detected using a UV spectrophotometer. The control group did not contain WS2 QDs or WS2QDs / RBC nanocomposite materials; all other aspects were the same.
[0078] like Figure 5 As shown in Figure a, compared with the control group, the UV absorption after the addition of WS2 QDs was significantly reduced, indicating that WS2 QDs can eliminate hydroxyl radicals, thereby reducing the generation of 2,3-dihydroxybenzoic acid. Moreover, compared with WS2 QDs, the WS2 QDs / RBC nanocomposite material has a stronger ability to eliminate hydroxyl radicals. (b) The figure shows the UV absorption peaks of the three curves, showing that the data of WS2QDs / RBC are significantly different from those of the control group (P < 0.05).
[0079] ②SOD enzyme-like activity assay: Dihydroethidium (HE) and superoxide radical (.O) 2- The reaction produces the fluorescent substance etidium (Ex = 470 nm, Em = 610 nm). First, an appropriate amount of 0.6 mM xanthine and 0.1 U / mL xanthine oxidase are mixed at 37 °C for 1 h to generate etidium. 2- Then, WS2 QDs and WS2 QDs / RBC from Example 1 were added and reacted for 40 min. Finally, HE dissolved in dimethyl sulfoxide (DMSO) was added and reacted for 40 min. The fluorescence intensity of ethidium was detected by a fluorescence spectrophotometer. The control group did not contain WS2 QDs or WS2 QDs / RBC nanocomposite materials, but the rest were the same.
[0080] like Figure 6 As shown in Figure a, compared with the control group, the fluorescence intensity decreased significantly after the addition of WS2 QDs, indicating a reduction in ethidium production. This is because WS2 QDs possess SOD enzyme activity, which can eliminate [the SOD]. 2- Furthermore, the SOD enzyme activity of WS2QDs / RBC was significantly stronger than that of WS2QDs. Figure b shows that the data of WS2QDs / RBC were significantly different from those of the control group (P < 0.05).
[0081] ③CAT enzyme activity assay: H2O2 reacts with KI in dilute sulfuric acid to produce I2. Since there is residual I- in the solution, I2 reacts with I-.- Combined into I3 - I3 - The material exhibits strong ultraviolet absorption at 350 nm, and this characteristic was used to investigate the CAT enzyme activity. WS2 QDs and WS2 QDs / RBC from Example 1 were added to centrifuge tubes, followed by an appropriate amount of H2O2. The tubes were incubated at 37°C for 6 hours. Finally, KI solution and dilute sulfuric acid were added, and the reaction was carried out for 10 minutes. The I3 concentration was detected using an ultraviolet spectrophotometer. - The UV absorption of the control group was the same as that of the control group, which did not contain WS2 QDs and WS2 QDs / RBC nanocomposite materials.
[0082] like Figure 7 As shown in Figure a, compared with the control group, the UV absorption intensity after adding WS2 QDs was significantly reduced, indicating that H2O2 was decomposed by the material, generating I3. - The reduced concentration and lower UV absorbance of the WS2 QDs / RBC system indicate stronger CAT enzyme-like activity. Figure b shows a significant difference between the WS2 QDs / RBC and control groups (P < 0.01).
[0083] In summary, the experiments demonstrate that the WS2 QDs / RBC nanocomposite material possesses excellent hydroxyl-removing ability, SOD enzyme-like activity, and CAT enzyme-like activity, indicating that it can effectively reduce oxidative stress and alleviate Alzheimer's disease symptoms.
[0084] (3) Cu in WS2 QDs / RBC nanocomposites 2+ Chelating ability;
[0085] The WS2 QDs and WS2 QDs / RBC from Example 1 were respectively mixed with Cu 2+ Mix 1:1, let stand for 30 min, and measure the remaining Cu using atomic absorption spectrometry (ICP). 2+ Concentration, calculating Cu in the material 2+ Chelation percentage.
[0086] like Figure 8 As shown in Figure d, the Cu of WS2 QDs 2+ The chelation percentage was only about 11%, but the chelation percentage of WS2 QDs / RBC reached 57.88%, indicating that the modification of the erythrocyte membrane significantly improved the Cu content of the material. 2+ Chelating ability, which can block Cu to some extent. 2+ It binds to Aβ fibrils, thereby reducing Aβ fibril toxicity.
[0087] (4) Investigation on the ability of WS2 QDs / RBC nanocomposites to inhibit Aβ monomer aggregation;
[0088] With Aβ 1-42 As a control, the WS2 QDs and WS2 QDs / RBC from Example 1 were compared with Aβ. 1-42 The monomers were incubated in a constant temperature shaking chamber at 37℃ for 2 days, and then an appropriate amount of 10mM thiosulfate-T (ThT) was added to react fully. The anti-Aβ monomer aggregation ability of the nanocomposite was investigated by enhancing its fluorescence intensity after ThT binds to Aβ fibrils (Ex = 444nm, Em = 482nm).
[0089] like Figure 9 As shown in Figure a, the fluorescence value of the WS2 QDs-added nanocomposite was significantly lower than that of the control group, and the fluorescence value of the WS2 QDs / RBC nanocomposite was even lower. This indicates that the nanocomposite can inhibit the aggregation of Aβ monomers into fibrils and reduce the concentration of Aβ fibrils to treat Alzheimer's disease. Figure b shows that the data of WS2 QDs / RBC compared with the control group were significantly different (P < 0.01).
[0090] (5) Investigation on the photothermal depolymerization ability of Aβ fibrils in WS2 QDs / RBC nanocomposites;
[0091] Using Aβ fibrils as a control, WS2 QDs and WS2 QDs / RBCs from Example 1, along with Aβ fibrils, were added to 96-well plates and incubated in a 37°C shaking incubator for 1 hour. The light-irradiated group was given near-infrared laser irradiation for 5 minutes (2W / cm²). 2 After incubating for 48 hours (808nm), add an appropriate amount of 10mM ThT and react fully. Measure the fluorescence value and plot the result.
[0092] like Figure 10 As shown in Figure a, the fluorescence value of WS2 QDs after illumination is lower than that without illumination, and the fluorescence value of WS2 QDs / RBC nanocomposite in Figure c is reduced more significantly. Figures b and d both show significant differences in the data. This indicates that the WS2QDs / RBC nanocomposite can effectively depolymerize Aβ fibrils and reduce their concentration by releasing heat energy under illumination, which can effectively treat Alzheimer's disease.
[0093] (6) Investigation on the cellular uptake capacity of WS2 QDs / RBC nanocomposites;
[0094] The WS2 QDs / RBC nanocomposite material from Example 1 was labeled with PE-FITC fluorescent dye and co-incubated with SY5Y cells. After 2 hours, the culture medium was aspirated, the culture dish was washed 2-3 times with PBS solution, the cells were fixed with 4% paraformaldehyde solution, stained with DAPI, washed again with PBS solution, and sealed with PVP anti-fluorescence quencher. Finally, the uptake of the WS2 QDs / RBC nanomaterial by the cells was observed under a laser confocal microscope.
[0095] like Figure 11 As shown, WS2 QDs / RBCs are stained green (a), SY5Y cell nuclei are stained blue (b), and in (c), the green and blue colors clearly overlap, indicating that the nanocomposite material was successfully taken up by the cells.
[0096] (7) Cytotoxicity investigation of WS2 QDs / RBC nanocomposites;
[0097] The cytotoxicity of WS2 QDs and WS2 QDs / RBC was determined using the MTT assay. WS2 QDs and WS2 QDs / RBC from Example 1 were diluted with pure water to different concentrations of 50 μg / mL, 25 μg / mL, 12.5 μg / mL, 6.25 μg / mL, and 3.125 μg / mL, respectively. These concentrations were then added to SY5Y cells and cultured in cell culture medium, with PBS as a control. After 24 h of incubation, the culture medium was aspirated from the wells, and an appropriate amount of thiazolyl blue solution was added to each well. After another 4 h of incubation, the thiazolyl blue was removed, and 100 μL of DMSO was added to each well to dissolve the crystals. Finally, the absorbance at 570 nm was measured using a microplate reader, and cell viability was calculated.
[0098] like Figure 12 As shown, different concentrations of WS2 QDs and WS2 QDs / RBC had no significant effect on cell survival, and the cell survival rate was higher than 90%, indicating that this nanocomposite material is non-cytotoxic and can be used as a safe and effective drug.
[0099] It should be noted that the specific embodiments described above enable those skilled in the art to gain a more comprehensive understanding of the present invention, but do not limit the present invention in any way. Therefore, those skilled in the art should understand that modifications or equivalent substitutions can still be made to the present invention; and all technical solutions and improvements that do not depart from the spirit and technical essence of the present invention should be covered within the protection scope of the present invention patent.
Claims
1. A method for preparing WS2 QDs / RBC nanocomposite material, characterized in that, Includes the following steps: (1) Dissolve nano-sized WS2 QDs powder in pure water and disperse it uniformly by ultrasonication to obtain a WS2 QDs dispersion; the particle size of WS2 QDs in the WS2 QDs dispersion is less than 60 nm; the concentration of the WS2 QDs dispersion is 0.1-2 mg / ml; (2) Extract animal blood as raw material for preparing red blood cell membranes; then mix the blood with heparin sodium solution to obtain a mixture; the animal blood is from mice, and the mouse species is any one of female BALB / c, female ICR, female C3H, and female RF; the volume ratio of the blood to the heparin sodium solution is 15-80:1; the mass concentration of the heparin sodium solution is 10 mg / ml; (3) Centrifuge the mixture obtained in step (2), collect the precipitate, add PBS and centrifuge and wash several times, and collect the precipitate to obtain pure red blood cells; Then PBS was added again to break down the red blood cells. After standing, the red blood cell membrane lysis solution was obtained. (4) Centrifuge the cell membrane disruption solution in step (3), then collect the precipitate, add PBS to wash several times, then wash with pure water, collect the precipitate, add PBS again to dissolve, and sonicate to disperse evenly to obtain red blood cell membrane dispersion. (5) Mix the WS2 QDs dispersion obtained in step (1) and the erythrocyte membrane dispersion obtained in step (4) in a certain proportion, stir overnight under constant temperature conditions, then centrifuge to discard the supernatant, collect the precipitate and add PBS solution, and ultrasonically disperse evenly to obtain WS2 QDs / RBC dispersion, which is WS2 QDs / RBC nanocomposite material; the mass ratio of erythrocyte membrane in the erythrocyte membrane dispersion to tungsten disulfide quantum dots in the WS2 QDs dispersion is 10:1-100:1; the temperature of the constant temperature stirring overnight is 37℃, and the stirring rate is 50-200 rpm; the ultrasonic power of the ultrasonic dispersion is 100 W-300 W, the ultrasonic time is 0.1 h-1.0 h, and the conditions are ice water bath; the concentration of the WS2 QDs / RBC dispersion is 0.1-2 mg / ml, calculated based on the mass of WS2 QDs.
2. The method for preparing a WS2 QDs / RBC nanocomposite material according to claim 1, characterized in that, The ultrasound in step (1) is performed in an ice-water bath using an ultrasonic cell disruptor with an ultrasonic power of 150 W-300 W and an ultrasound time of 0.1 h-1.0 h.
3. The method for preparing a WS2 QDs / RBC nanocomposite material according to claim 1, characterized in that, In step (3), the centrifugation speed is 2000 rpm / min-5000 rpm / min and the centrifugation time is 5 min-20 min; the settling temperature is 0-4℃ and the settling time is 0.5 h-2 h.
4. The method for preparing a WS2 QDs / RBC nanocomposite material according to claim 1, characterized in that, In step (3), the concentration of PBS used during centrifugation and washing is 0.01M, and the number of washes is 3-5 times; the concentration of PBS used when adding PBS to break down red blood cells is 0.0025M.
5. The method for preparing a WS2 QDs / RBC nanocomposite material according to claim 1, characterized in that, In step (4), the centrifugation speed is 5000 rpm / min-14000 rpm / min and the centrifugation time is 10 min-30 min; the ultrasound is performed under ice-water bath conditions, the ultrasound power is 100 W-300 W and the ultrasound time is 0.1 h-1.0 h. The concentration of the PBS is 0.01M; the concentration of the red blood cell membrane dispersion is 100 mg / ml.
6. The WS2 QDs / RBC nanocomposite material prepared by the method according to any one of claims 1-5.
7. The use of the WS2 QDs / RBC nanocomposite material according to claim 6 in the preparation of anti-Alzheimer's disease drugs.
Citation Information
Patent Citations
Preparation method and application of layered molybdenum disulfide-erythrocyte membrane nanocomposite
CN114533887A
